FORMS OF PUBLIC-PRIVATE PARTNERSHIP (PPP) AND THEIR APPLICATIONS IN NIGERIA - T. E., Oyigbo; Ugwu, Prof. O. O.; Nnadi, Dr. EOE (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
It has become imperative to study the features of the various models with a view to ensuringsuitable application with increased application of Public-Private Partnership (PPP) as thepanacea for infrastructure development and maintenance in most states of the country, Theresearch employed review research design of which available journals, reports, textbooks, gazettesand newspapers sourced the information needed. Literature reveals the need for increasedawareness of PPP, which is capital intensive with potency of complicated legal tussle, if notproperly understood. The paper also analyzed the challenges militating against the implementationof PPP agreements in the country. It is thus, recommended that stakeholders in the areas of PPPshould be adequately trained and enabling laws domesticated in each state of the federation inorder to develop public infrastructure in the current reality